The Role of Immigration Technical Staff For The Service and Protection of Indonesian Citizens at The Indonesian Consulate General In Johor Bahru - Rendy Ilyandi; Muhammad Syaroni Rofii (International Journal Labs, 2025)
This study aims to examine the role of Immigration Technical Staff in providing services and protection for Indonesian citizens (WNI) within the jurisdiction of the Consulate General of the Republic of Indonesia (KJRI) in Johor Bahru. Employing a descriptive qualitative approach and case study method, this research analyzes various immigration services, including passport issuance, Travel Document in Lieu of Passport (SPLP), visas, dual citizenship affidavits, and citizenship renunciation documents. Additionally, it investigates the protective functions for problematic Indonesian nationals, such as those facing deportation, overstaying, neglect, and legal violations. The findings indicate that Immigration Technical Staff not only fulfill administrative duties but also act as state representatives in implementing protection diplomacy and strengthening both individual and national resilience. Within the theoretical framework of law, individual resilience, national resilience, and protection, the presence of Immigration Technical Staff is a tangible manifestation of the state's responsibility to its citizens abroad.